(sfi)2 Statistics for Innovation – The experience of the Oslo centre in industrial statistics. (January 2015) - Frigessi, Arnoldo; Holden, Lars; Teigland, André; Kenett, Ron; Shmueli, Galit
<x xml:space="preserve">Abstract</x> Statistics is one of the paramount sciences of the 21st century because of the emergence of the value of data as a key asset for development. It is of fundamental importance to deliver statistical methods and tools for the progress of science and sustainable economic growth. Statistics for Innovation (sfi)2 has been, between 2007 and 2014, a centre of excellence providing new statistical methodology for selected Norwegian industries and service providers. In this paper, we trace the history of (sfi)2, describe the way it operated and the type of projects it has run over 8 years. We discuss challenges and the way we tried to overcome them. The purpose of this paper is to share our experience for similar centres, outline the advantages and challenges and indicate some recommendations. Copyright © 2015 John Wiley & Sons, Ltd.